Pertanggungjawaban Pidana terhadap Pemilik Tempat Hiburan Malam Atas Peredaran Narkotika di Kota Jambi - Sumaidi Sumaidi (Universitas Batanghari Jambi, 2021)
Regarding the circulation of Narcotics in nightclubs, it is regulated in Article 35 to Article 44 of Law 35 of 2009 concerning Narcotics so that this study aims to determine the criminal responsibility of owners of nightclubs for the distribution of narcotics, especially in the city of Jambi and explain the efforts that conducted to tackle the circulation of narcotics in night entertainment venues in the city of Jambi. The method in this research is juridical empirical and the scope of research studied is the circulation of narcotics and the object studied is a nightclub in the city of Jambi. The materials used are field materials and library research. Data collection techniques, namely document studies related to documents in accordance with the subject matter. The analysis technique in this research is qualitative. Criminal responsibility for the owners of nightclubs for the distribution of narcotics, especially in the Jambi City area has not been implemented so that efforts made, namely the Jambi City Police Resort with the Provincial Narcotics Agency and the National Narcotics Agency must carry out raids on visitors and commercial sex workers, as well as entertainment business owners. night in Jambi City.